Straty inteligencji polskiej w czasie II wojny światowej na przykładzie mordu dokonanego w Stanisławowie = The Stanisławow atrocity, one of many examples of the losses of Polish intelligentsia during World War II - Kulińska, Lucyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During and immediately after World War II, the systematic elimination of the Polish people employed in the educational sector took place in Poland. The perpetrators of these crimes were the occupying forces of Germany and Russia, with the active cooperation of non-Polish national minorities living in the territory of the Second Polish Republic.
Keywords: Second World War; Stanisławów; Extermination; killing; murders; teachers; intelligentsia; Polish people; Germans; eksterminacja; morderstwo; zabójstwo; nauczyciele; inteligencja; Niemcy; Rosjanie; Polacy